A case of gamma 3 heavy chain disease with vacuolated plasma cells: a clinical, immunological, and ultrastructural study. Issue 4 (April 1979) - Feremans, W; Caudron, M; Bieva, C
Abstract : A patient with lambda Bence-Jones proteinuria, Waldenström's macroglobulinaemia, and Franklin's disease (gamma HCD), but without clinical evidence of a lymphoproliferative disorder, is presented. The serum contained two distinct immunoglobulin abnormalities: a monoclonal immunoglobulin M (IgM) of lambda type, and a protein fragment which was immunologically related to immunoglobulin G (IgG) and devoid of light chain activity. This gamma HCD protein belongs to the gamma 3 subclass with a molecular weight of approximately 60, 000 daltons. The urine contained a Bence-Jones lambda protein as well as the gamma HCD fragment. The two paraproteins were probably secreted by two different malignant clones. Ultrastructural study revealed pathological vacuolated plasma cells of a sort that has hitherto been principally described in association with micron HCD. The mechanism of the intracellular storage of pathological immunoglobulins is discussed in the light of the ultrastructural study.